Upgrade methods for improving availability and disaster resilience of telecommunication networks - Nunes, Pedro José Jorge Barata (2020)
In current societies, telecommunication networks are one of its essential components, in which different services depend on. Critical service requires these networks to provide high levels of availability between their nodes and high levels of resilient to large-scale natural disasters, either by avoiding them or quickly recover from them. Different techniques can be used to reach these goals. In this dissertation, it is considered the use of geodiversity routing to reduce the impact of large-scale disasters, with the downside of utilizing longer paths which, in turn, reduces the resulting end-to-end availability. This downside can be corrected if the availability of some network elements are upgraded so that the availability required by critical services is met, while maintaining the geodiversity required to prevent the impact of disasters. In this dissertation, different upgrade strategies are implemented to efficiently identify the network elements required to be upgraded, so that the network can provide critical services with high availability and high resilience to natural disasters.